Dutch for reading knowledge. - Baalen, Christine van (John Benjamins Publishing Company, 2012)
This first Dutch for Reading Knowledge book on the market promotes a high level of reading and translation competency by drawing from Dutch grammar, vocabulary and reading strategies, and providing many translation "shortcuts" and tips when tackling complex texts in Dutch. Aimed at students, researchers and scholars who need to learn how to read and translate modern Dutch texts for their academic research, this book focuses on those areas where the Netherlands plays or has played a leading and innovative role in the world. These areas include architecture, art history, design, the Dutch Golden.